2021
DOI: 10.1016/j.jhin.2021.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of five SARS-CoV-2 rapid antigen detection tests in a hospital setting and performance of one antigen assay in routine practice: a useful tool to guide isolation precautions?

Abstract: Background In a hospital setting, there is a need for rapid detection of SARS-CoV-2 to guide isolation measures and targeted admission. Aim First, we evaluated the diagnostic performance of five SARS-CoV-2 rapid nucleocapsid protein antigen detection (RAD) assays (Biosynex, Biotical, Orient Gene, Panbio, SD Biosensor). Secondly, we described the performance and impact of the implementation of the SD Biosensor assay at our emergency department. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…The Biosynex ® rapid antigenic diagnostic tests turned out to be effective. Their sensitivity between 90% and 100% and specificity between 70% and 99% have been shown to be similar to RT-PCR tests [9][10][11]. False negatives were rare.…”
Section: Determination Of Contagiousnessmentioning
confidence: 75%
“…The Biosynex ® rapid antigenic diagnostic tests turned out to be effective. Their sensitivity between 90% and 100% and specificity between 70% and 99% have been shown to be similar to RT-PCR tests [9][10][11]. False negatives were rare.…”
Section: Determination Of Contagiousnessmentioning
confidence: 75%
“…Like MERS-CoV, virus antigen test was generally reported to have lower sensitivity (<80%) in detecting the specific antigen of SARS-CoV-2, especially when this test was compared to the molecular diagnostic test like qRT-PCR [249] , [250] , [251] , [252] In terms of the test specificity, antigen test was found to be most specific (>90%) to detect SARS-CoV-2 without creating cross-reaction when other respiratory pathogens were present [249] , [250] , [251] , [252] , [253] , [254] , [255] , [256] , [257] . However, there was also some study which had reported that the antigen test results could have low specificity (as low as 46.2%) and this suggested that antigen test could be used in rapid screening of the SARS-CoV-2 infection but the use of other confirmatory tests like qRT-PCR should be conducted to confirm the viral infection [258] . As for the molecular target that is frequently used in the virus antigen test, both N and S antigens of SARS-CoV-2 are the commonly employed antigenic targets in the virus antigen test, and the LOD to detect these antigenic targets could range from 100,000 RNA copies in 1 mL to 2.86 ×107 RNA copies in a single swab [253] , [256] .…”
Section: Different Diagnostic Approaches To Detect Mers-cov and Sars-cov-2 Infectionsmentioning
confidence: 99%
“…Specificity is consistently reported to be high. Sensitivity compared to rRT-PCR is highly variable (0-94%) and related to the viral load, with higher sensitivity reported on samples with higher viral load [2]. They would be useful for screening and diagnosis on a large scale as well as in countries with limited resources.…”
Section: Introductionmentioning
confidence: 99%